Effect of medicinal plant extracts on mycelial growth of Pleurotus florida - RS, Aparna; Gangadharan, Heera; Susha, ST; Sreeja, SJ (Mushroom Research, 2022)
A study was conducted at Department of Plant Pathology to evaluate the effect of medicinal amendments in edible species of oyster mushroom, Pleurotus florida. The medicinal plants viz., Adathoda (Justicia vasica), neem (Azadirachta indica) and ocimum Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â (Ocimum sanctum) were used as amendments. The dried and powdered leaves of the medicinal plants were used for assessing their efficacy. In vitro evaluation was carried out with the medicinal amendments using poisoned food technique. Adathoda (Justicia vasica), Neem (Azadirachta indica) and Ocimum (Ocimum sanctum) was amended in potato dextrose agar medium (PDA) at 250, 500 and 1000 ppm concentrations along with control. The experiment was laid out in Completely Randomized Design with ten treatments and four replication. Nature of mycelial growth, rate of mycelial growth (cm day-1) and days taken for completion of growth in petri dish were observed. The mycelium of P. florida in amended medium produced white sparse growth with fluffy centre later turning to whitish fluffy growth with regular margin whereas in control plate the mycelium was with white sparse growth later turning to white cottony with regular margin on full growth in petri dish. The rate of mycelial growth was highest in control (1.6 cm day-1). The days taken for complete mycelial growth in petri dish ranged from 7 to 8 among the various amendments used. The addition of medicinal amendments was not inhibitory to the mycelial growth of P.florida indicating its use in biomedicinal enrichment with pharmaceutical properties.Â